Память о вечном: стихи / Владимир Емельянов - Емельянов Владимир Иванович (Удмуртия, 1979)
Экземпляры: ЧЗ (20160414) / Инвентарный номер: 14603 / Цена: 0.20 / Сис.шифр: Р2 / Авт.знак: Е 60 / ГРНТИ: 17 / ББК: 84(2)